Revealing Slang Words Used by Generation Z on Social Media "TikTok" - Shinta Ramadhani, Anastasya; Pujiyatno , Ambar (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
Language manifests in various forms, particularly among the younger generation. Generation Z, in particular, demonstrates a stronger inclination toward using slang in everyday communication rather than formal language. This study aims to investigate the use of slang words by Generation Z on the widely used social media platform, TikTok. Employing a descriptive qualitative method with a sociolinguistic approach, this research adopts the theoretical framework of Allan and Burridge (2006), who categorize slang into five types: fresh and creative, flippant, imitative, acronym, and clipping. The findings of this study revealed 50 slang word entries used by Generation Z TikTok users in 2025. The analysis showed that the slang words fell into five categories: fresh and creative (23%), flippant (12%), imitative (18%), acronym (30%), and clipping (18%). Among these, acronyms were found to be the most frequently used slang type, with a proportion of 30%. This dominance is attributed to their practicality, brevity, and effectiveness in message delivery—characteristics that align with Generation Z's preference for fast, creative, and easily comprehensible modes of communication.